Analytical Expressions for Bulk Modulus of Fullerene C60 in Case of Nonlinear Volumetric Deformations - Van Thang, Nguyen; Hoang Oanh, Nguyen; Huy Kien, Bui; Duc Luong, Vu; Duc Hung, Pham (VNU Journal of Science: Mathematics - Physics; Vol 40 No 2DO - 10.25073/2588-1124/vnumap.4889, 2024)
The aim of this work is to establish the bulk modulus expressions of fullerene C 60 in both linear and nonlinear deformation cases. The Lennard-Jones potential energy is used to calculate the bonding forces between carbon atoms. The research results reveal a formula demonstrating the dependence of the bulk modulus on the volume of the fullerene in the case of significant volume deformation (nonlinear case). Consequently, the bulk modulus of fullerene C 60 can be determined basing on the volume deformation ratio. A comparison between the bulk modulus in general case (large deformation - nonlinear) and specific case (small deformation - linear) has been made. The results obtained through the Finite Element Method (FEM) and Density function theory (DFT) have affirmed the accuracy of the research results.